Discriminative ability of balance tests in single- and dual-task conditions between copers and chronic ankle instability - Pirayeh, Nahid; Shahbazi, Aida; Mostafaee, Neda; Kosarian, Zahra (Physiotherapy theory and practice, 2025)
Previous studies have examined the ability of balance tests to distinguish between individuals with chronic ankle instability (CAI) and healthy controls. To investigate accuracy and determine cutoff scores of balance tests in single- and dual-task conditions in discriminating between copers and individuals with CAI. Seventy subjects (35 subjects in each group) participated in the study. Static and dynamic balance were evaluated using single-leg stance, side hop, figure-of-8 hop, and Y-balance test in single- and dual-task conditions. A cognitive task used in the study was backward counting by seven, starting from a random number, between 200 and 300. The accuracy of these tests was determined by calculation of sensitivity, specificity, area under receiver operating characteristic (ROC) curve (AUC), likelihood ratios (LRs) and predictive value (PV). The ROC curve showed, except for posterior-lateral direction of Y-balance test, all balance tests had good ability for discrimination between two groups of coper and CAI. Also, the highest sensitivity (0.97 (95% confidence interval (CI): 0.84-0.99)) and the lowest amount of negative LR (0.05 (95% CI: 0.00-0.35)) and negative PV (0.95 (95% CI: 0.73-0.99)) were related to single-leg stance. While the highest specificity (0.82-0.88) and greatest positive LR (5-5.75) and positive PV (0.83-0.85) were related to side hop test, single-leg stance, figure-of-8 hop, and the posterior-medial direction of Y-balance test in dual-task condition. Investigating the static and dynamic balance under dual-task conditions could have added value to correctly identifying balance deficit in individuals with CAI.